Chymase mediates injury and mitochondrial damage in cardiomyocytes during acute ischemia/reperfusion in the dog. - Junying Zheng; Chih-Chang Wei; Naoki Hase; Ke Shi; Cheryl R Killingsworth; Silvio H Litovsky; Pamela C Powell; Tsunefumi Kobayashi; Carlos M Ferrario; Andras Rab; Inmaculada Aban; James F Collawn; et al. (PLoS ONE, 2014)
Cardiac ischemia and reperfusion (I/R) injury occurs because the acute increase in oxidative/inflammatory stress during reperfusion culminates in the death of cardiomyocytes. Currently, there is no drug utilized clinically that attenuates I/R injury in patients. Previous studies have demonstrated degranulation of mast cell contents into the interstitium after I/R. Using a dog model of I/R, we tested the role of chymase, a mast cell protease, in cardiomyocyte injury using a specific oral chymase inhibitor (CI). 15 adult mongrel dogs had left anterior descending artery occlusion for 60 min and reperfusion for 100 minutes. 9 dogs received vehicle and 6 were pretreated with a specific CI. In vivo cardiac microdialysis demonstrated a 3-fold increase in interstitial fluid chymase activity in I/R region that was significantly decreased by CI. CI pretreatment significantly attenuated loss of laminin, focal adhesion complex disruption, and release of troponin I into the circulation. Microarray analysis identified an I/R induced 17-fold increase in nuclear receptor subfamily 4A1 (NR4A1) and significantly decreased by CI. NR4A1 normally resides in the nucleus but can induce cell death on migration to the cytoplasm. I/R caused significant increase in NR4A1 protein expression and cytoplasmic translocation, and mitochondrial degradation, which were decreased by CI. Immunohistochemistry also revealed a high concentration of chymase within cardiomyocytes after I/R. In vitro, chymase added to culture HL-1 cardiomyocytes entered the cytoplasm and nucleus in a dynamin-dependent fashion, and promoted cytoplasmic translocation of NR4A1 protein. shRNA knockdown of NR4A1 on pre-treatment of HL-1 cells with CI significantly decreased chymase-induced cell death and mitochondrial damage. These results suggest that the beneficial effects of an orally active CI during I/R are mediated in the cardiac interstitium as well as within the cardiomyocyte due to a heretofore-unrecognized chymase entry into cardiomyocytes.